El afuera interior (2019)
The purpose of this project was to explore the genesis of interior atmospheres, based on their relationships with exterior and interior spaces. How does the atmosphere of a private space configure, in relation to other private spaces and to the public space? I sought to discover the intangible of each physical place, that is, what allowed a certain psychic disposition in the space. This atmosphere was thought out as a hybrid element, both objective and subjective, that is, as the limit of the human being ?with his thoughts, affections, customs, etc.? and the space that receives him, all of which constitutes the life of the habitant. So, I wondered what the genesis of that atmosphere was, that hybrid element. I called this process of genesis atmosphericization. And to study it, I made use of architectural, artistic and philosophical references that, in different ways, have spoken of this hybrid element of space, tangible and intangible, visible and invisible alike.